2023
DOI: 10.1002/trtr.2237
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual Learning Inside/Outside the Classroom: Insights from Intra‐Active Events

Marsha Jing Ji Liaw,
Maria José Botelho,
Sunny Man Chu Lau

Abstract: As K‐5 dual language programs gain popularity in the United States, language teaching, however, often still prioritizes discrete and decontextualized learning that is not built on students’ interests and experiences or their multilingual and multimodal resources. This article reports on a classroom‐based ethnographic case study and illustrates how emergent bilinguals in a fifth grade dual language class engaged in a variety of multimodal experiences to understand local history through their first and second la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Studies focusing on teachers' take-up of translanguaging pedagogy in DLI programs are limited. Also, most translanguaging studies address English/Spanish translanguaging practices (Hamman, 2018;Palmer et al, 2014), while only a few have discussed non-Spanish/English contexts such as Mandarin/English DLI (Du, 2022;Liaw et al, 2023;Tian, 2022;Tian & Lau, 2023;Zheng, 2021). For example, Zheng (2021) examined the translanguaging discourse of a 4th/5th-grade Mandarin teacher.…”
Section: Translanguaging Pedagogymentioning
confidence: 99%
See 3 more Smart Citations
“…Studies focusing on teachers' take-up of translanguaging pedagogy in DLI programs are limited. Also, most translanguaging studies address English/Spanish translanguaging practices (Hamman, 2018;Palmer et al, 2014), while only a few have discussed non-Spanish/English contexts such as Mandarin/English DLI (Du, 2022;Liaw et al, 2023;Tian, 2022;Tian & Lau, 2023;Zheng, 2021). For example, Zheng (2021) examined the translanguaging discourse of a 4th/5th-grade Mandarin teacher.…”
Section: Translanguaging Pedagogymentioning
confidence: 99%
“…The teacher offered significant autonomy for students to choose their preferred languages and modalities, which led to enhanced language and subject learning outcomes. Liaw et al (2023) also collaborated with a 5th-grade Mandarin teacher in developing an interactive history curriculum where translanguaging pedagogy was adopted to help students better contextualize content knowledge and assemble all available resources for their writing. The study suggested that teachers made moment-by-moment pedagogical adjustments as they drew on students' first language in the learning of a second/additional language.…”
Section: Translanguaging Pedagogymentioning
confidence: 99%
See 2 more Smart Citations